EFEKTIVITAS PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) MELALUI GERAKAN STOP BUANG AIR BESAR SEMBARANGAN (BABS) DI DESA PAWALUTAN KECAMATAN BANJANG KABUPATEN HULU SUNGAI UTARA - Noorrahman, Moh. Fajar (PPPM STIA Amuntai, 2020)
The development of the health sector is an effort carried out by all components with the aim of increasing awareness, willingness and ability to live a healthy life so that there is an increase in the degree of public health. One of the efforts to improve the degree of public health is through the Sanitasi Total Berbasis Masyarakat (STBM).. The implementation of the program, which is carried out with five pillars, namely Stop Buang air besar Sembarangan, Cuci Tangan Pakai Sabun , Pengelolaan Air Minum dan Makanan Rumah Tangga, Pengamanan Sampah Rumah Tangga dan Pengamanan Limbah Cair Rumah Tangga is aimed at facilitating efforts to improve access to community sanitation better and changing and maintaining a sustainable culture of clean and healthy living. The negative potential is generally not realized by the community, especially for people in remote areas, most of them still open defecation in river areas due to the lack of knowledge of the surrounding community about health. Pawalutan Village, Hulu Sungai Utara District, where out of 293 families, only 128 families have a toilet in their house while those who do not have a toilet are recorded as 165 families. Research method Using a qualitative method with purposive sampling technique. The research subjects were elements of the Pawalutan village government, a number of local villagers, and several related parties. Based on the discussion of the research results, it can be concluded that the effectiveness of the Sanitasi Total Berbasis Masyarakat (STBM). through the Stop Open Defecation Movement in Pawalutan Village, Banjang District, Hulu Sungai Utara Regency, is classified as not yet effective in terms of various aspects of program success, aspects of target success, aspects of satisfaction with the program. aspects of the level of input and output comparisons then aspects of achieving the overall goal.